KONSEP TUHAN MENURUT AL-GHAZALI: TAFSIR AYAT CAHAYA - Agus Supriyanto (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2006)
Imam Al-Ghazali (1058-11J1) is one of the greatest muslim scholars who delivered a lot of Islamic thoughts in varied disciplines such as Islamic law, ethics, philosophy, mysticism and theology. Within theological realm, for example, he explores the existence of God. According to his view, in accordance with Surah Al-Nur verse 35, God or Allah is Light of the heavens and the earth. The Light is true light in substance, which differs from other lights. Then Allah is the True Light and other lights or creatures are the artificial lights. In short, Allah as the True Light illuminates and enlightens all the creatures.